2017
DOI: 10.1111/jgh.13834
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive diagnosis of hepatic fibrosis by BioFibroScore® in chronic hepatitis C patients

Abstract: Background and Aims: The diagnostic accuracy of a novel serological panel (BioFibroScore

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Baseline demographics, hemogram, international normalized ratio, serum albumin, total bilirubin, aspartate aminotransferase, alanine aminotransferase, and eGFR, which was assessed by modification of diet in renal disease equation, anti‐HCV, hepatitis B virus (HBV) surface antigen (Abbott Architect HBsAg qualitative assay, Abbott Laboratories, Abbott Park, Illinois, USA), HCV RNA, and HCV genotype (Abbott RealTi me HCV Genotype II, Abbott Laboratories, Abbott Park, Illinois, USA), were collected for all patients . Cirrhosis was determined by liver biopsy, imaging studies, signs of portal hypertension, aspartate aminotransferase‐to‐platelet ratio index with a cutoff value of > 2.0 or liver stiffness measurement (FibroScan®, Echosens, Paris, France) with a cutoff value of > 12.5 kPa when appropriate …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline demographics, hemogram, international normalized ratio, serum albumin, total bilirubin, aspartate aminotransferase, alanine aminotransferase, and eGFR, which was assessed by modification of diet in renal disease equation, anti‐HCV, hepatitis B virus (HBV) surface antigen (Abbott Architect HBsAg qualitative assay, Abbott Laboratories, Abbott Park, Illinois, USA), HCV RNA, and HCV genotype (Abbott RealTi me HCV Genotype II, Abbott Laboratories, Abbott Park, Illinois, USA), were collected for all patients . Cirrhosis was determined by liver biopsy, imaging studies, signs of portal hypertension, aspartate aminotransferase‐to‐platelet ratio index with a cutoff value of > 2.0 or liver stiffness measurement (FibroScan®, Echosens, Paris, France) with a cutoff value of > 12.5 kPa when appropriate …”
Section: Methodsmentioning
confidence: 99%
“…26 Cirrhosis was determined by liver biopsy, imaging studies, signs of portal hypertension, aspartate aminotransferase-to-platelet ratio index with a cutoff value of > 2.0 or liver stiffness measurement (FibroScan®, Echosens, Paris, France) with a cutoff value of > 12.5 kPa when appropriate. [27][28][29] Patients received SOF in combination with RBV, DCV, or DCV for 12 weeks. For SOF/RBV regimen, they received SOF (Sovaldi®, 400 mg per tablet, Gilead Sciences, Carrigtohill, Co. Cork, Ireland) 1 tablet per day in combination with weight-based RBV (Robatrol®, 200 mg per capsule, Genovate Biotechnology Co. Ltd., Hsinchu, Taiwan; 1200 mg per day if the body weight-75 kg; 1000 mg per day if the body weight < 75 kg).…”
Section: Methodsmentioning
confidence: 99%
“…Patients were included in the study if they were aged 20-70 years, had documented chronic HCV infection that was defined as detectable HCV antibody (anti-HCV; Abbott HCV EIA 2.0, Abbott Laboratories, Abbott Park, Illinois, USA) and/or serum HCV RNA level > 1000 IU/mL (Cobas TaqMan HCV Test v2.0, Roche Diagnostics GmbH, Mannheim, Germany, lower limit of quantification [LLOQ]: 15 IU/mL) for ≥ 6 months, had HCV GT1b infection (Abbott RealTime HCV genotype II, Abbott Molecular Inc. Illinois, USA), had estimated glomerular filtration rate < 15 mL/min/1.73m 2 as assessed by the Modification of Diet in Renal Disease Study equation, had received hemodialysis, were non-cirrhotic that were confirmed by liver biopsy or liver stiffness measurement (LSM, FibroScan, Echosens, Paris, France) with a cut-off value of < 12.5 kPa, and had HCV RNA level > 10 000 IU/mL at screening visit. [21][22][23] Patients were excluded from the study if they were infected with HCV genotypes other than HCV GT1b, had hepatitis B virus (HBV), or human immunodeficiency virus (HIV) coinfection, had decompensated cirrhosis (Child-Pugh B or C), had active hepatocellular carcinoma at screening visit, had history of malignancy (except for cutaneous melanoma) within 5 years of screening, had received organ transplantation (except for prior renal transplantation with graft failure), had prior exposure of DAAs, host-targeting agents, or therapeutic vaccines for HCV, were pregnant, were unwilling to have contraception during the study period, or refused to provide informed consent for the study. Patients were also excluded from the study if the hemoglobin level < 10 g/dL, absolute neutrophil count < 1.50 × 10 9 cells/L, platelet count < 60 × 10 9 cells/L, international normalized ratio (INR) > 2.0, serum albumin level < 2.8 g/dL, serum total bilirubin level > 3.0 mg/dL, serum aspartate aminotransferase (AST), or alanine aminotransferase (ALT) quotient > 5, or serum alpha fetoprotein level (AFP) > 100 ng/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline demographic, data hemogram, international normalised ratio (INR), serum biochemical profiles (albumin, bilirubin, aspartate aminotransferase [AST], alanine aminotransferase [ALT], creatinine, estimated glomerular filtration rate [eGFR], as calculated by Cockcroft‐Gault equation), anti‐HCV, hepatitis B virus (HBV) surface antigen (HBsAg) (Abbott Architect HBsAg qualitative assay, Abbott Laboratories, Abbott Park, Illinois, USA), HCV RNA, HCV genotype (Abbott RealTime HCV Genotype II, Abbott Laboratories, Abbott Park, Illinois, USA) and anti‐HIV (Abbott Architect HIV Ag/Ab Combo, Abbott Laboratories, Abbott Park, Illinois, USA) were collected for all patients . Each patient received transient elastography (FibroScan, Echosens, Paris, France) to assess the stage of hepatic fibrosis . In patients with confirmed cirrhosis, the severity was graded by Child‐Pugh score.…”
Section: Methodsmentioning
confidence: 99%